What Is the Value of Sovereign Ratings?. Issue 1 (27th June 2013) - Gaillard, Norbert
Abstract This article gives a fresh analysis of sovereign ratings, including the recent default of Greece. Section 1 studies the evolution of the sovereign rating business, and Section 2 explains how credit ratings are assigned. Section 3 focuses on sovereign rating methodologies and identifies the key determinants of sovereign ratings. Section 4 measures the accuracy of these ratings between 1 January 2001 and 1 January 2013. Section 5 compares credit ratings to market‐based indicators, and Section 6 concludes.